Implementasi Fungsi Manajemen Sekolah dalam Pengelolaan Program Tahfidz: (Studi Kasus SD Kuttab Imam Syafi’I Brebes) - Aji Riswanto; Mohamad Maftuh Fauzi (EBISMAN eBisnis Manajemen, 2026)
The Qur'an memorization (tahfidz) program is designed to enhance students' ability to memorize the Qur'an while instilling Islamic values from an early age. The success of this program depends on effective school management through the implementation of management functions. This study aims to analyze the management functions in the tahfidz program at SD Kuttab Imam Syafi’i Brebes. Using a qualitative approach with a case study design, data was collected through observation, interviews, and documentation. The subjects included the school principal, tahfidz program coordinator, teachers, and students. Data analysis followed the stages of data reduction, presentation, and conclusion drawing. The findings show that management functions at SD Kuttab Imam Syafi’i Brebes are carried out through four main functions: planning, organizing, actuating, and controlling. Planning involves setting objectives, memorization targets, and choosing suitable learning methods. Organizing includes dividing responsibilities between the principal, coordinator, and teachers. The tahfidz program involves activities like muroja’ah (memorization review), adding new memorization, and teacher submission. Supervision is conducted through regular evaluations and meetings. The study concludes that effective management function implementation is crucial for the success of the tahfidz program, aiding in the achievement of educational goals in memorizing the Qur'an.